Empowerment technologies - Lujero, Rosalie P. (Quezon City : Vibal Group Inc., 2018)
"This book offers students an in-depth look at how information and communications technologies (ICT) can impact our lives for the better. It highlights how proper use of ICT allow individuals to create their own content, collaborate, and increase productivity. More importantly, the textbook explores how ICT can become a medium to promote positive social change".
Includes bibliography and glossary.
English text.
Keywords: Information technology; Computer networks